Evidence of validity of the Mini International Personality Item Pool - Simkin, Hugo (2020)
Background: the five-factor model represents one of the most widely used approaches to the study of personality from a psychological perspective. Although many instruments have been relied upon for its evaluation, the Mini International Personality Item Pool (Donnellan et al., 2006) is one of the main tools highlighted in the literature. Objective: for this reason, the purpose of the present study is to adapt and validate such instrument in a non-probability sample composed of university students in Buenos Aires (N = 2460). Results: a confirmatory factor analysis indicates a good fit to the data of the model relayed by the authors, so it can be recommended to be administered in the local context. Conclusion: it is suggested that future works explore their properties in different populations. Contribution of authorship HS: design and design of the studio, interpretation of the data and final review of the manuscript. LBD: interpretation of the data and final review of it manuscript. SA: interpretation of the data and final review of it manuscript.